Applications of field programmable gate arrays for engine control - Viele, Matthew, author; Willson, Bryan D., advisor; Marchese, Anthony J., committee member; Meroney, Robert N., committee member; Troxell, Wade O., committee member (Colorado State University. Libraries, 2012)
Automotive engine control is becoming increasingly complex due to the drivers of emissions, fuel economy, and fault detection. Research in to new engine concepts is often limited by the ability to control combustion. Traditional engine-targeted micro controllers have proven difficult for the typical engine researchers to use and inflexible for advanced concept engines. With the advent of Field Programmable Gate Array (FPGA) based engine control system, many of these impediments to research have been lowered. This dissertation will talk about three stages of FPGA engine controller application. The most basic and widely distributed is the FPGA as an I/O coprocessor, tracking engine position and performing other timing critical low-level tasks. A later application of FPGAs is the use of microsecond loop rates to introduce feedback control on the crank angle degree level. Lastly, the development of custom real-time computing machines to tackle complex engine control problems is presented. This document is a collection of papers and patents that pertain to the use of FPGAs for the above tasks. Each task is prefixed with a prologue section to give the history of the topic and context of the paper in the larger scope of FPGA based engine control. The author of this study founded, built up, and eventually sold Drivven Inc., a company dedicated to the implementation of FPGAs in engine control. As a result, this study spans a decade of time where we see the first few papers related to FPGA based engine control, and concludes with FPGA based engine controllers being the de facto standard for advanced combustion research.
Keywords: CFD; engine control; FPGA; free-piston; hydraulic; real-time